Finding Martyrs at Home?: Jesuit Attempts at Redefining Martyrdom in the Seventeenth Century and Their Censure - Gay, Jean-Pascal (Journal of Jesuit studies, 2022)
Pope Francis’s recent recognition of the death of several priests active in Guatemala in the 1980s as martyrdom has reminded the public of a long-term hesitation within Catholicism as to the boundaries of martyrdom. Key aspects of the history of this hesitation played out in the seventeenth century. Several religious orders—most prominently the Jesuits—argued for a redefinition of martyrdom that would include the so-called “martyrdom of charity” (i.e. the death of those who had imperiled their lives to care for the sick). Among the theologians that entered the fray to advocate for such a redefinition, the most prominent is certainly Theophile Raynaud (the “new Bellarmine” of the mid seventeenth century) whose De martyrio per pestem was censured with other texts that promoted the same position, when the Inquisition decided to take a stand against the campaign for the redefinition of martyrdom. By studying Raynaud’s and other treatises, as well as their censure, this paper will try to assess the significance of this debate for Jesuit history and that of early modern Catholicism. It will try and show how it connected with the theological controversies of the time but also how it pertained to an issue within the order, namely that of the hierarchy of ministries that sometimes weighed on how the order operated, particularly in Europe.